EFFECT OF DROUGHT STRESS ON PHYSIOLOGICAL GROWTH PARAMETERS OF TOMATO INBRED LINES AT GERMINATION STAGE - Kibreab M. Ghebremariam; Liang Yan; Zhengcai Zhang; Qiaoli Wang (European Scientific Journal, ESJ, 2013)
This study was carried out to investigate the effect of water stress condition in growth parameters of 35 tomato inbred lines. Those inbred lines are collected from different countries and they were screened with osmotic concentration of 12.5 % polyethylene glycol 6000 while their respective control treatments were treated using distilled water for twelve days at germination stage. The relative percentages of shoot length, root length, shoot weight; root weight and relative germination rate were computed to determine the effect of water stress on the growth parameters of the inbred lines. According the experiment’s result, drought tolerant inbred lines have longer root length and higher root weight than the susceptible inbred lines. Shoot length and shoot weight was not much affected by the drought situation at the germination stage. The most drought tolerant inbred lines have the highest relative germination rate and the drought susceptible inbred lines have a lower relative germination rate. The highest germination percentage was recorded at control treatments than in the PEG treatments.